Aplicação de técnicas de gestão avançada Lean Helthcare para otimizar o fluxo de pacientes do pronto-socorro de um hospital universitário público de Belo Horizonte - Melissa Prado de Brito (2018)
Introduction: The overcrowding of emergency services is a worldwide phenomenon and can lead to a many of problems, including unfavorable outcomes in the treatment and evolution of patients. Waiting time for medical care and average length of stay are key performance indicators for emergency and emergency services. Reducing these indicators can improve the quality of care by providing agility in accessing diagnosis and treatment for the patient's condition. Objective: To demonstrate the use of the Lean Helthcare methodology in optimizing the flow of patient care in an Emergency and Emergency Unit of a public university hospital. Method: This is an exploratory and descriptive case study carried out at the Emergency and Emergency Unit of the Hospital das Clínicas of the Federal University of Minas Gerais. The flow of patients was analyzed in the period between admission to the first medical reevaluation. The research was developed in four stages: (1) Identification of Current Value Flow, from the application of the concepts Lean Healthcare; (2) identification of opportunities for improvement; (3) proposing improvement interventions; and (4) projection of the gains and benefits generated with the implementation of the Future Value Flow Map. Results: Long waiting time and opportunity to reduction were identified. Following the implementation of the Lean Healthcare methodology, the expected reduction in waiting time is 100% for patient access to risk classification, 30% for admission to initial medical evaluation, for nursing assessment and between assessment and the first medical reassessment; and 55% between the request and the availability of laboratory and image exams. There was a 33.7% reduction in Lead Time and a 42% improvement in the percentage of value added. Conclusion: The study demonstrated that the implementation of the Lean Healthcare methodology can promote improvements in the efficiency of process performance in emergency services and may contribute to reduce overcrowding